ANALISIS KLASTER PAUTAN LENGKAP UNTUK MENGELOMPOKKAN KABUPATEN/KOTA DI PROVINSI SULAWESI TENGAH BERDASARKAN INDIKATOR KRIMINALITAS - Utami, I T; Rais, Rais; Seftiani, W (Program Studi Matematika, Universitas Tadulako, 2019)
Criminality is all kinds of actions and deeds which is economically and psychologically harmful. The statistical method could be used to classify the crime is cluster analysis. Cluster analysis is a multivariate method which aims to classify a sample of subjects (or objects) on the basis of a set of measured variables into a number of different groups such that similar subjects are placed in to the same group. The objective of this research is to classify Regency/City in Central Sulawesi Province based on the criminality indicator and to discover the profile of each cluster which had been formed. The results of the study shows that those are two clusters formed: Cluster 1 consists of Buol, Banggai, Morowali, Toli-Toli, Donggala, and Tojo Una-Una Regency; Cluster 2 consists of Regency/Palu City, and Parigi Moutong. The profile of each cluster is: Cluster 1 with low crime rate on average and Cluster 2 with high crime rate on average.Keywords : Cluster Analysis, Complete Linkage, Criminality, Hierarchy Method.